PENGENDALIAN GULMA PADA TANAMAN KEDELAI DENGAN MENGGUNAKAN BEBERAPA WAKTU APLIKASI MULSA ORGANIK KIRINYUH (Chromolaena odorata L.) - Amda Resdiar; Hasanuddin Hasanuddin; Siti Hafsah (Universitas Teuku Umar, 2020)
Utilization of mulch could reduce competition between weeds and soybean crop for water, light, nutrient, maintaining temperature and humidity of soil to create better growth of soybean environment. Soybean crop had a critical period of weeds competition so that siam weed organic mulch should be applied to control weeds at certain time. The research aims to improve the yield of soybean crop that is influenced by application times of siam weed mulch. This study had defferent time of mulch aplications treatment such as at the time of planting, 7 days after planting (DAP), and 14 DAP. The results of this reserch showed that application times had not effected significantly at all parameter. The result also showed the earlier application time of siam weed organic mulch it was on planting time had decreased weed growth then increased yield of soybean. Keywords: Weed, soybeans, mulch, application time